STRATEGI KOMUNIKASI PERSUASIF DALAM AKTIVITAS PEMASARAN (Studi Deskriptif Komunikasi Persuasif Presenter (Staff Pemasaran) dalam Merekrut Calon Mahasiwa baru di Politeknik LP3I Jakarta) - Syamsurizal Syamsurizal (POLITEKNIK LP3I JAKARTA, 2016)
This study is titled Persuasive Communication Strategy Presenter (Staff Marketing) in the Candidate Acceptance of new Students at the Polytechnic LP3I Jakarta. The purposes of research are to investigate the persuasive communication strategies used Presenter (Staff Marketing), Presenter persuasive communication process, and behavioral changes that occur in prospective students. The theory used in the study are: Interpersonal Communication, Persuasive Communication, and AIDA. This study used a qualitative descriptive study and narrated by interpretive. Information obtained through observation and in-depth interviews (in-depth interviews) to Four Presenters Polytechnic LP3I Jakarta have been recruited as an informant. Results from this study is the presenter strategy to convince new students through persuasive communication emotional and personal approach.Keywords : Persuasive Communication, Presenter (Staff Marketing), Marketing Pemasaran